Acceptability of Babies Conceived through Assisted Reproductive Technology among Married Women in University of Benin Teaching Hospital, Benin City, Nigeria - Olorunfemi, Olaolorunpo; Osian, Eunice Amaechi; Oahimijie, Florence Onyemaechi (CHRISMED Journal of Health and Research, 2021)
Infertility is a condition whereby a married woman is unable to et pregnant despite having frequent unprotected sex for at least a year. This has been an area of medicine in which health care practitioners has limited means to help their patients. The landscape of this fields changed dramatically with the announcement of birth through the of Assisted Reproductive Technology (ART) by Louise Brown in 1978. This has given hope to millions of couples suffering from infertility
Keywords: Ngozi Rosemary Osunde; Rachael Olufunmilayo Oduyemi; Assisted; infant; newborn; Nigeria; reproductive techniques; ACE: Reproductive Health Innovation; CERHI; University of Benin